2015
DOI: 10.1063/1.4922950
|View full text |Cite
|
Sign up to set email alerts
|

Phonon bottleneck in GaAs/AlxGa1−xAs quantum dots

Abstract: We report low-temperature photoluminescence measurements on highly-uniform GaAs/AlxGa1−xAs quantum dots grown by droplet epitaxy. Recombination between confined electrons and holes bound to carbon acceptors in the dots allow us to determine the energies of the confined states in the system, as confirmed by effective mass calculations. The presence of acceptor-bound holes in the quantum dots gives rise to a striking observation of the phonon-bottleneck effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…If this is compared with the total 2D density of states calculated for the ground state for the InAs QWs, which is shown in Figure (c) (1×10 13 cm −2 ), then it becomes clear that the increased contribution of the high energy tail is not the result of significant state‐filling, or the saturation of the ground‐state, and therefore likely has its origin in inhibited hot carrier relaxation via the creation of a phonon bottleneck . Similar effects have been observed recently in InAs QDs, where the spatial separation of carriers in impurity states leads to the observation of inhibited carrier relaxation as a result of reduced carrier–carrier scattering . The type‐II nature of InAs/AlAsSb is expected to lead to similar results here.…”
Section: Experimental Results and Analysissupporting
confidence: 75%
“…If this is compared with the total 2D density of states calculated for the ground state for the InAs QWs, which is shown in Figure (c) (1×10 13 cm −2 ), then it becomes clear that the increased contribution of the high energy tail is not the result of significant state‐filling, or the saturation of the ground‐state, and therefore likely has its origin in inhibited hot carrier relaxation via the creation of a phonon bottleneck . Similar effects have been observed recently in InAs QDs, where the spatial separation of carriers in impurity states leads to the observation of inhibited carrier relaxation as a result of reduced carrier–carrier scattering . The type‐II nature of InAs/AlAsSb is expected to lead to similar results here.…”
Section: Experimental Results and Analysissupporting
confidence: 75%
“…1(c) (1×10 13 cm −2 ), then it becomes clear that the increased contribution of the high energy tail is not the result of significant state-filling, or the saturation of the ground-state, and therefore likely has its origin in inhibited hot carrier relaxation via the creation of a phonon bottleneck 7 . Similar effects have been observed recently in InAs QDs, where the spatial separation of carriers in impurity states leads to the observation of inhibited carrier relaxation as a result of reduced carrier-carrier scattering 26 . The type- II nature of InAs/AlAsSb is expected to lead to similar results here.…”
Section: Experimental Results and Analysissupporting
confidence: 83%
“…Figure 7 shows PL measurements at temperatures from 4 K to 100 K, which contain a range of emission peaks. At 4 K, an intense peak at 689 nm (Peak 1) is observed from recombination of Al 0.32 Ga 0.68 As layer electrons to heavy holes (hh) in the QR valence band [15]. Another peak (Peak 2) can be distinguished at 706 nm, which we attribute to recombination of electrons in the Al 0.32 Ga 0.68 As with holes bound to a carbon impurity acceptor state (A 0 ) within the QR [15].…”
Section: As 2 and As 4 Crystallisation Comparisonmentioning
confidence: 99%
“…At low temperature, electron access to pathways for relaxation is limited, suppressing transitions from GaAs QR states and causing peak 1 to be dominant. Peak 2 has low intensity, as it has been shown that it is associated with the presence of the phonon-bottleneck, which limits relaxation of electrons to A 0 [15]. As the temperature is raised above 4 K, an increase in available hh states lift the phonon bottleneck and suppress peak 2.…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation